Buccal Bioadhesive Drug Delivery System: An Overview - Patel, Kinesh V (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Buccal administration of drugs provides a convenient route of administration for both systemic and local drug actions. However, the preferred site for retentive oral transmucosal delivery systems and for sustained- and controlled-release delivery devices is the buccal mucosa, mainly because of the differences in permeability characteristics between the two regions and the buccal mucosa’s expanse of smooth and relatively immobile mucosa. Key advantages and limitations related to the buccal drug delivery system has also been discussed in the review. In the development of these buccal drug delivery systems, mucoadhesion of the device is a key element. Mucoadhesive polymers have been utilized in many different dosage forms in efforts to achieve systemic delivery of drugs through the buccal mucosa. This article reviews current status of various buccal bioadhesive dosage forms such as tablets, patches, hydrogels and chewing gums and describes the strategies to improve permeation of drugs through the Buccal mucosa. Recent innovations in the dosage form development and in vivo and in vitro mucoadhesion testing methods has also been focused. Lastly, different dissolution testing methods for buccoadhesive dosage forms developed by different researchers have also been discussed.